Penerapan SSOP (Sanitation Standard Operational Procedure) Pada Produksi Udang (Litopenaeus vannamei) Breaded di PT. Tri Mitra Makmur Situbondo Jawa Timur - Lailia Khuriyyatus Sa’adah; Siti Nur Aisyah Jamil (Faculty of Science and Technology University Ibrahimy, 2024)
Shrimp is a type of food that is categorized as a perishable food or also known as deterioration of quality, so it requires proper handling and processing to minimize the activity of several pathogenic bacteria. The handling procedure related to this is known as Hazard Analysis Critical Control Point (HACCP) which includes the application of sanitation hygiene called Standard Sanitation Operating Procedure (SSOP). This study aims to determine the implementation of SSOP carried out at PT. Tri Mitra Makmur Situbondo Regency, which is a large food industry, with its implementation on July - September 2023. The methodology used is descriptive methods with the primary and secondary data. The data was undertaken by observation follow directly all the the process which began with the raw materials to loading and interview. Results obtained, 7 of 8 keys that start with 1. )Water and ice safety, 2 The. )Food contact, 3 The. )Cross-contamination Prevention, 4 The. )Hand washing and toilets, 5 The. )Protection of contaminants, 6 The. )Label, storage, and toxin management, 7 The. )Healthcare workers, 8 The. )The pest control is done., but a little obstacle on the key of the hand washing place and the toilet.This happens because it is not in accordance with the number of toilets that are in there with the number of employees who work.These barriers can affect products due to contamination so that it will reduce the quality of the productivity of the food processing unit. Keywords: Shrimp, SSOP, Perishable food